Rasio Produksi terhadap Konsumsi Beras di Kota Banjarbaru (Tahun 2002-2012) - Grace Natalia; Emy Rahmawati; Dolok Saribu (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
Kota Banjarbaru has agricultural potency to produce rice even though the sector is not the flagship sector. The capability to change from rice deficit in to rice surplus under limited land is very challenging. Therefore, the study describing current condition of rice surplus and deficit is important to give information and to support the agricultural policy making, especially rice production policy. Thus, the study is addressed to describe: (1) rice production; (2) rice consumption; (3) rice surplus and minus; (4) the production-consumption ratio; and (5) the factor influenced rice consumption in Kota Banjarbaru. Ordinary least square (OLSJ were used to estimate F-test, t-test, and determination coefficient (R). During 2002, Kota Banjarbaru needed additional 53.16% of total rice consumption to meet the local demand. The rice production and consumption rati o ranged between 0.24 and 0. 72. Based on regression model, harvested acreage and productivity affect rice production positively. On the consumption model, population gives positive impact on rice consumption. Interestingly, income per capita negatively affects rice consumption. Both factors affect the rice consumption significantly.